Scale of Teacher Support Related to Career and Impact Validation Assessment of its Effect on Career Decision Making Self-Efficacy - Arif Sahin; Dwi Yuwono Puji Sugiharto; Sunawan Sunawan; Mulawarman Mulawarman (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Adolescents often rely on support from significant adult figures particularly parents and teachers to navigate their career development, yet research exploring the specific influence of teacher support on students’ career-related outcomes remains limited. This study aims to examine the factorial structure and measurement invariance of the Indonesian adaptation of the Teacher Support Scale (TSS). Using a quantitative survey design, the study involved 662 high school students who completed the Indonesian version of the TSS consisting of 21 items across four dimensions. Data were analyzed using multi-group confirmatory factor analysis (CFA) to assess configural, metric, scalar, and strict invariance across gender. The findings demonstrate that the Indonesian TSS exhibits strong internal reliability and retains its four-factor structure consistently for both male and female students. Furthermore, all invariance models met acceptable fit criteria, indicating that the scale functions equivalently across gender groups. These results confirm that the TSS is suitable for assessing teacher support related to career decision-making self-efficacy among adolescents. The study’s implications highlight the importance of teacher-based interventions in strengthening students’ career confidence and informing future practices in career guidance and counseling.